The trouble of sex: Sex-determination, prenatal diagnosis and politics - Lisa Lindén (The Royal Danish Library, 2018)
Recent decades have seen the rapid development of assisted reproductive technologies (ARTs) and methods of prenatal diagnosis. As a result, there are now several ways to predict the genetic sex of embryos as well as visualizing the sex of fetuses. However, how, when and where these technologies may be used have become politicized questions, both internationally and in Sweden. By providing a close reading of the Swedish political debate about technologies for the determination of the sex of fetuses and embryos from the end of the 1980s onwards, this article shows how technologies of prenatal diagnosis are articulated as problematic in the context of sex-determination. By “staying with the trouble” of sex in the political debate about sex-determination, we discuss how the ability to identify fetal or chromosomic sex through prenatal diagnosis is articulated as an unwanted trouble warranting political and ethical concern. The article also highlights the “ethico-political” restrictions imposed on information about the unborn’s sex. It shows that, rather than prenatal diagnosis enabling promissory or hopeful visions of the future, the political debate is preoccupied with feelings of concern about the potential misuses of these technologies.